The Effect of Affiliate Marketing on Trust and Repurchase Intention: A Study of Tokopedia Marketplace in Pontianak City - Maulidya, M; Sumiyati, S (Journal of Economics and Management Scienties, 2025)
This study aims to analyze the effect of Affiliate Marketing on Trust and Repurchase Intention on Tokopedia marketplace users in Pontianak City. The method used is a quantitative method with an associative approach. Primary data was obtained through a questionnaire to 200 respondents who are Tokopedia users. The independent variable in this study is Affiliate Marketing, the mediator variable is Trust, and the dependent variable is Repurchase Intention. Data analysis was carried out using the Structural Equation Modeling (SEM) technique through SmartPLS software. The results of the study indicate that Affiliate Marketing has a positive and significant effect on Trust, Trust has a positive and significant effect on Repurchase Intention, but Affiliate Marketing does not have a direct effect on Repurchase Intention. However, it was found that Trust significantly mediates the effect of Affiliate Marketing on Repurchase Intention. This finding shows the importance of consumer trust in strengthening the effectiveness of affiliate marketing strategies to encourage repeat purchases. This study provides implications for e-commerce players in designing marketing strategies that focus on increasing customer trust through an affiliate approach.